Забезпечення безпеки та енергостійкості транспортної інфраструктури у воєнний період - Родіонов, М. М. (Національний університет "Львівська політехніка", 2025)
The article examines the issue of ensuring energy sustainability in the transport sector in Ukraine's frontline regions during wartime. The study identifies key factors that determine the stability of transport energy, including decentralization of energy supply, integration of alternative energy sources, and digitization of monitoring systems.
Keywords: транспорт; транспортна інфраструктура; сталий розвиток; транспортна енергетика; транспортні системи; енергетична безпека